Biodegradable plant pots made from dried banana pseudo‐stems enriched with a Bacillus sp.‐biochar composite as an eco‐friendly alternative to plastic pots - Sangsuwan, Parisatcha; Detraksa, Janejira; Inchomrit, Pranitda (Indonesian Journal of Biotechnology, 2025)
Agricultural plastic waste is a major environmental pollutant due to its non‐biodegradable nature. This study discusses the production of biodegradable pots (bio‐pots) using a biochar composed of banana pseudo‐stems and Bacillus sp. The isolated Bacillus sp. produced indole‐3‐acetic acid (IAA), solubilized potassium and phosphate, and secreted siderophores immobilized in banana pseudo‐stem biochar. X‐ray diffraction analysis revealed CaCO3 and KCl as the major elements, aside from carbon, released to the soil. Bio‐pots were made from banana pseudo‐stem biochar mixed with a Bacillus sp.–biochar composite at various formulations: 0%, 1%, 3%, 5%, and 10%. Mechanical testing indicated that the porous structure of the biochar contributed to low pot density and tensile strength. Moreover, the air‐filled spaces within the biochar enhanced water absorption, correlating with the amount of biochar used. Marigolds were cultivated outdoors in the bio‐pots to assess growth and yield. Our findings showed that those grown in biopot‐4 (10%) displayed improved growth and yield compared to the control group (grown in the ground). After 10 weeks, the control plants became infected with fungi and aphids, whereas those grown in biopot‐4 remained unaffected. In summary, bio‐pots incorporating 10% Bacillus sp.–biochar are eco‐friendly, reducing the need for chemical fertilizers, fungicides, and insecticides, while contributing to environmental sustainability. Moreover, the combination of biochar and Bacillus sp. is more effective than an unmixed form, since Bacillus sp. can inhabit and propagate in biochar pores if the conditions are otherwise unsuitable for growth.